2017
DOI: 10.1111/ejn.13724
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of multisensory reliability and perceptual weights emerge at early latencies during audio‐visual integration

Abstract: To make accurate perceptual estimates, observers must take the reliability of sensory information into account. Despite many behavioural studies showing that subjects weight individual sensory cues in proportion to their reliabilities, it is still unclear when during a trial neuronal responses are modulated by the reliability of sensory information or when they reflect the perceptual weights attributed to each sensory input. We investigated these questions using a combination of psychophysics, EEG-based neuroi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 71 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…To link pre-stimulus activity with perception we used the same statistical modelling approach as in our previous study (Kayser et al., 2016). We computed pre-stimulus activity in task-relevant EEG components extracted using multivariate linear discriminant analysis (Boyle et al., 2017; Kayser et al., 2016; Parra et al., 2005; Philiastides, 2006; Ratcliff et al., 2009). We searched for discriminant components within the EEG data that best discriminated between the frequency conditions (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…To link pre-stimulus activity with perception we used the same statistical modelling approach as in our previous study (Kayser et al., 2016). We computed pre-stimulus activity in task-relevant EEG components extracted using multivariate linear discriminant analysis (Boyle et al., 2017; Kayser et al., 2016; Parra et al., 2005; Philiastides, 2006; Ratcliff et al., 2009). We searched for discriminant components within the EEG data that best discriminated between the frequency conditions (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this reaffirms our assumption that associative congruency shapes multisensory decision formation, thus improving either or both the speed and accuracy of choice. Similarly, multisensory enhancements during perceptual decision formation have been found with interactions occurring in neural signals at very short latencies ( Boyle et al., 2017 ; Cappe et al., 2010 ; Foxe et al., 2000 ; 2002 ; Foxe and Schroeder, 2005 ; Molholm et al., 2002 ; 2006 ; Sperdin et al., 2009 ). Importantly, in our study the early modulation we observed suggests such enhancements are not exclusively multisensory, since on each trial only a single sensory stimulus was presented.…”
Section: Discussionmentioning
confidence: 84%
“…This way we revealed latencies and electrodes where VEP amplitudes increase with cue reliability at the same rate that behavioral discriminability increases with reliability. Previous work studied how information about uncertain sensory evidence is neurally represented and by linking this representation to behavioral outcomes they suggested a unified psychophysical-neural model (Boyle et al, 2017;Philiastides & Sajda, 2006). The main advantage of our methodology lies in establishing an equivalence with the sensitivity to cue reliability (i.e.…”
Section: Discussionmentioning
confidence: 99%